PENGARUH PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA GORONTALO - Trisusanti Lamangida; Umar Sako Baderan; Rukiyah R. Saridi (Universitas Muhammadiyah Gorontalo, 2019)
This study aims to determine how much influence restaurant tax has on local revenue (PAD) in Gorontalo City. The research method uses a quantitative approach with descriptive quantitative types. The results showed that: 1) There is a positive relationship or in statistical techniques it is said to have an influence relationship, when an increase in one variable is accompanied by an increase in the value of other variables, and sometimes followed by an increase in the value of other variables, with the equation: Y = 87,801,873,155, 883 + 10,518X, 2) The magnitude of the relationship or variable correlation with the result is 0.996. Based on the calculation of the test criteria, the relationship between restaurant tax and Local Own Revenue of 0.996 has a very strong variable relationship, 3) Based on the calculation results, the tcount value is 17.261 and the ttable value is 2.35336, because the tcount value is smaller than the ttable value. It is concluded that restaurant tax does not have a significant effect on Regional Original Income (PAD). Keywords: Restaurant Tax, Local Revenue